Digging for bird-dinosaurs : an expedition to Madagascar - Bishop, Nic, 1955- (Boston [Mass.] : Houghton Mifflin, 2000)
The story of Cathy Forster's experiences as a member of a team of paleontologists who went on an expedition to the island of Madagascar in 1998 to search for fossil birds.
Includes bibliographical references (p. 46) and index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
6.2.
6.9
Keywords: Forster, Cathy -- Travel -- Madagascar; Forster, Cathy; Forster, Cathy; Birds, Fossil -- Madagascar -- Juvenile literature; Dinosaurs -- Madagascar -- Juvenile literature; Birds, Fossil -- Madagascar; Dinosaurs -- Madagascar; Birds -- Madagascar; Dinosaurs -- Madagascar; Fossils; Madagascar; Madagascar